The Structural and Macroeconomic Determinants of Manufacturing Export-Value Performance in ASEAN Countries - Jonathan Andersen; Albert Hasudungan; Salvarina Viknesuari; David Tjie; Handoko Sukarno; Erica Novianti Lukas (Universitas Hayam Wuruk Perbanas, 2023)
This study aims to scrutinize the determinants of manufacturing exports in several ASEAN countries, specifically: Indonesia, Malaysia, Thailand, Philippines, and Vietnam. It adopts a panel data regression using the random effects model to predict manufacturing export value using structural (economic complexity and human capital) and macroeconomic (real effective exchange rate, foreign direct investment, and inflation) variables. The research finds that foreign direct investment, human capital, real effective exchange rate, and inflation are positive and statistically significant predictors of manufacturing exports in these ASEAN countries. However, the positive correlation between the real effective exchange rate and manufacturing exports is against previous literature arguing that a currency’s depreciation drives export competitiveness. The findings suggest that currency appreciation can enhance a country’s export performance as exports’ input products are cheaper than before. Additionally, the positive influence of inflation on exports can be explained by the subsequent increase in consumption from foreign countries. Therefore, in addition to managing their exchange rates, countries must develop their human capital and attract more foreign investments to enhance their export performance.